ANALISIS HUKUM TERHADAP PERANAN DAN TANGGUNG JAWAB KOMISARIS INDEPENDEN DALAM PERSEROAN TERBUKA (STUDI PADA PT. TOBA PULP LESTARI Tbk) - Susanto Susanto (PREMISE LAW JURNAL, 2013)
Since the kind of company obtains its capital from the public, there are many stakeholders who have an interest in it. The urgency of the existence of an independent supervisor in one company is undeniably very important. An independent commissioner plays an important role. Generally, a corporation is managed by a stockholder manager. A corporation which collects its capital from the public needs more control because it deals with public interest. The Indonesia Stock Exchange and Bapepam (Capital Investment Supervisory Board) regulates the status of independent commissioners more specifically besides Law No.40/2007 on Corporation.They regulate that in the statues of a corporation, a corporation can assign at least one independent commissioner and one representative commissioner. Beside that, every corporation should specify one article in its statues about responsibility of an independent commissioner for realizing the principles of good corporate governance in a corporation in Indonesia.